AGRESIFITAS SUPIR BIS KOTA YANG BERETNIS BATAK DAN TINGKAT KAPATUHAN BERLALU LINTAS - alatas, maryam (Prodi Ilmu Hukum Universitas Nahdlatul Ulama Indonesia, 2021)
This study aims to see a picture of the aggression behavior of city bus drivers and to find out the things that trigger aggression behavior in city bus drivers and their correlation with legal compliance of city bus drivers in traffic. Data collection techniques in this study were interviews and observations. The research subjects in this study were city bus drivers aged 30-40 years who have worked as bus drivers for at least one year and are of Batak ethnicity. In addition to interviews with the subject, researchers also conducted interviews with the significant other which is the subject's kernet. The results showed that the subjects engaged in aggressive behavior both physically, verbally, actively, passively and directly or indirectly, which was triggered by several factors, namely, frustration, stress, deindividuation, power and obedience, provocation and air temperature. This is a factor in the low level of legal compliance of bus drivers in traffic. Keywords: aggression, city bus driver, adherence, traffic.